Biocompatible, High‐Performance, Wet‐Adhesive, Stretchable All‐Hydrogel Supercapacitor Implant Based on PANI@rGO/Mxenes Electrode and Hydrogel Electrolyte. Issue 30 (21st June 2021) - Liu, Yang; Zhou, Hui; Zhou, Weixiao; Meng, Si; Qi, Cheng; Liu, Zhou; Kong, Tiantian
Abstract: Functional bioelectronic implants require energy storage units as power sources. Current energy storage implants face challenges of balancing factors including high‐performance, biocompatibility, conformal adhesion, and mechanical compatibility with soft tissues. An all‐hydrogel micro‐supercapacitor is presented that is lightweight, thin, stretchable, and wet‐adhesive with a high areal capacitance (45.62 F g −1 ) and energy density (333 μWh cm −2, 4.68 Wh kg −1 ). The all‐hydrogel micro‐supercapacitor is composed of polyaniline@reduced graphene oxide/Mxenes gel electrodes and a hydrogel electrolyte, with its interfaces robustly crosslinked, contributing to efficient and stable electrochemical performance. The in vitro and in vivo biocompatibility of the all‐hydrogel micro‐supercapacitor is evaluated by cardiomyocytes and mice models. The latter is systematically conducted by performing histological, immunostaining, and immunofluorescence analysis after adhering the all‐hydrogel micro‐supercapacitor implants onto hearts of mice for two weeks. These investigations offer promising energy storage modules for bioelectronics and shed light on future bio‐integration of electronic systems. Abstract : An all‐hydrogel micro‐supercapacitor implant that is lightweight, thin, stretchable, and wet‐adhesive with a high areal capacitance (45.62 F g −1 ) and energy density (333 μWh cm −2, 4.68 Wh kg −1 ) is presented. Its in vitro and in vivo biocompatibility as an integrative implant is evaluated by cardiomyocytes and mice models. These investigations offer promising energy storage modules for future bio‐integrative electronic systems.